2021
DOI: 10.1016/j.ijid.2021.07.041
|View full text |Cite
|
Sign up to set email alerts
|

BCG vaccination induces enhanced frequencies of dendritic cells and altered plasma levels of type I and type III interferons in elderly individuals

Abstract: Babu , BCG vaccination induces enhanced frequencies of dendritic cells and altered plasma levels of type I and type III interferons in elderly individuals, International

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…As early as July 17, 2020, ICMR-National Institute for Research in Tuberculosis conducted a phase 3 clinical trial to evaluate the effectiveness of the BCG vaccine in decreasing morbidity and mortality of elderly individuals with COVID-19 in India (NCT04475302). COVID-19COVID-19COVID-19The preliminary results observed the proliferation of plasma-like dendritic cells and myeloid dendritic cells and increased levels of IFN-λ1 (IL-29), IFN-λ2 (IL-28a), and IFN-λ3 (IL-28b) and decreased levels of IFN-α and IFN-βin plasma induced by BCG vaccination [141] . These results provide indirect evidence for BCG vaccination to fight SARS-CoV-2 infection by enhancing heterologous immunity.…”
Section: Is the Bcg Vaccine Effective Against Sars-cov-2 Infection?mentioning
confidence: 95%
See 1 more Smart Citation
“…As early as July 17, 2020, ICMR-National Institute for Research in Tuberculosis conducted a phase 3 clinical trial to evaluate the effectiveness of the BCG vaccine in decreasing morbidity and mortality of elderly individuals with COVID-19 in India (NCT04475302). COVID-19COVID-19COVID-19The preliminary results observed the proliferation of plasma-like dendritic cells and myeloid dendritic cells and increased levels of IFN-λ1 (IL-29), IFN-λ2 (IL-28a), and IFN-λ3 (IL-28b) and decreased levels of IFN-α and IFN-βin plasma induced by BCG vaccination [141] . These results provide indirect evidence for BCG vaccination to fight SARS-CoV-2 infection by enhancing heterologous immunity.…”
Section: Is the Bcg Vaccine Effective Against Sars-cov-2 Infection?mentioning
confidence: 95%
“… Positive (indirect evidence): BCG vaccination was associated with enhanced DC subsets and IL-28A/IL-29 in elderly individuals, suggesting its ability to induce non-specific innate immune responses. [141] Clinical trial* 301 elderly Greek patients BCG revaccination resulted in 68% risk reduction for total COVID-19 clinical and microbiological diagnoses. Positive: BCG revaccination resulted in reduction for total COVID-19 clinical and microbiological diagnoses.…”
Section: Is the Bcg Vaccine Effective Against Sars-cov-2 Infection?mentioning
confidence: 99%
“…Blood was drawn from the controls only at baseline. The demographic and epidemiological data have been previously reported [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, when BCG-DCs were co-cultured with human cord-blood mononuclear cells, they produced anti-inflammatory cytokine IL-4, which may partially contribute to low protection garnered by BCG. In the elderly, a study surveying whole blood and plasma samples 1 month post BCG immunization observed enhanced plasmacytoid and myeloid DCs ( 259 ). Despite this, plasma levels of type I IFNs (IFNα/β) were significantly decreased, while type III IFNs (l), which comprise anti-viral cytokines (also named IL-28A, IL28B, and IL-29), were significantly enhanced, potentially showcasing the off-target effects of BCG ( 259 ).…”
Section: Cell Subsets Widening the Viewmentioning
confidence: 99%
“…In the elderly, a study surveying whole blood and plasma samples 1 month post BCG immunization observed enhanced plasmacytoid and myeloid DCs (259). Despite this, plasma levels of type I IFNs (IFNa/b) were significantly decreased, while type III IFNs (l), which comprise anti-viral cytokines (also named IL-28A, IL28B, and IL-29), were significantly enhanced, potentially showcasing the off-target effects of BCG (259). Next-generation BCG vaccine candidates may also work to improve and direct BCG-induced i n fl a m m a t o r y D C a c t i v a t i o n a s a p r o p o s a l f o r enhanced protection.…”
Section: Dendritic Cellsmentioning
confidence: 99%